Volatile organic compounds produced by Metschnikowia pulcherrima yeast T-2 inhibited the growth of Botrytis cinerea in postharvest blueberry fruits - Zhuoran Li; Quanyong Liu; Chenyang Wu; Yujin Yuan; Xuemei Ni; Tianyi Wu; Ruokui Chang; Yuanhong Wang (Horticultural Plant Journal)
Postharvest rot of blueberry fruits caused by Botrytis cinerea led to huge economic losses in storage and transportation. In this study, Metschnikowia pulcherrima T-2 was isolated from the surface of blueberry fruits and significantly reduced postharvest rot of blueberry fruits. The weight loss rate of T-2 soaked blueberry fruits was decreased; the contents of total soluble solids, titratable acidity and vitamin C of T-2 treated blueberry fruits were increased at a humidity of 85% and 25 °C. T-2 also enhanced the control of gray mold in blueberry fruits, but could not directly inhibit the growth of B. cinerea in vitro. The volatile organic compounds (VOCs) produced by T-2 could inhibit the growth of B. cinerea, and significantly reduced the postharvest rot of blueberry fruits. According to Gas Chromatography-Mass Spectrometry (GC–MS) analysis and antibacterial analysis, the benzyl alcohol, phenylethyl alcohol, benzaldehyde, 2-ethyl-1-hexanol, acetic acid, octanoic acid, 3-hydroxy-2-butanone, 2, 5-dimethyl-pyrazine and isoamyl acetate were selected. The influence of the above 9 volatiles on B. cinerea growth was assessed by treating B. cinerea in vitro with various concentrations of volatile. The lowest effective amounts of 9 volatiles were established to reduce the postharvest rot of blueberry fruits. These results shed light on the roles of T-2 VOCs in the control of postharvest blueberry fruits to B. cinerea, and provided a new method of postharvest storage.